Procedural success and safety of a standardized less invasive surfactant administration protocol using fentanyl premedication and video laryngoscopy in preterm infants <32 weeks’ gestation - Popa-Todirenchi, Mircea-Horia; Bubl, Benedikt; Keller, Fabian; Busso, Marta; Jaisli, Sophie; Bünte, Lisa Marie; Oestreich, Marc-Alexander; Kidszun, André (Frontiers in Pediatrics, 2025)
BackgroundLess Invasive Surfactant Administration (LISA) has been established for treating respiratory distress syndrome (RDS) in preterm infants, but the impact of pharmacological analgesia or video laryngoscopy on procedural success and safety remains unclear. We evaluated procedural success and adverse events of LISA performed according to a standardized protocol incorporating intravenous opioid analgesia and video laryngoscopy assistance.MethodsThis single-center, retrospective, observational study was conducted at a tertiary neonatal unit from September 2021 to August 2023. All live-born infants <32 weeks’ gestation were screened. Exclusion criteria were parental objection to data use, missing primary outcome data, major congenital malformations, prenatal palliative care decisions, outborn transfered after 24 h of life or already receiving invasive ventilation. The LISA protocol comprised the administration of intravenous fentanyl (1 µg/kg) 3–5 min prior to video laryngoscopy, followed by delivery of Poractant alfa (100–200 mg/kg) via a thin oral catheter. The primary endpoint was first-attempt success. Secondary endpoints comprised the frequency of procedure-related adverse events, including bradycardia (HR <80 bpm), desaturation (SpO₂ < 80%), number of LISA attempts, arterial hypotension, and LISA failure, defined as intubation with subsequent mechanical ventilation within 72 h.ResultsOf 243 live-born infants, 63 were excluded from analysis. Of the remaining 180 infants 84 (47%) received LISA, 45 (25%) were intubated in the delivery room and 51 (28%) remained on non-invasive ventilation without surfactant. In the LISA cohort (median gestational age: 29 + 3 weeks; mean birth weight: 1,176 g), fentanyl was administered to 83/84 patients (99%), and video laryngoscopy was used in 82/84 patients (98%). First-attempt success was achieved in 52/84 (62%) infants. Attending physicians had a significantly higher probability of first-attempt success than interns (OR 4.86, 95% CI 1.40–16.80, p = 0.013). Periprocedural bradycardia occurred in 6 infants (7%), desaturation in 65 infants (77%) and post-procedure hypotension in 6 infants (7%). LISA failure occurred in 14/84 (17%) infants.ConclusionThis study provides detailed data on the procedural quality of LISA when opioid analgesia and video laryngoscopy are used. This data may inform future trials investigating analgesia strategies, safety, and long-term outcomes.